Surface modification of banana fibers by DBD plasma treatment - Oliveira, F. R. (2012)
Banana fibers, an environmentally friendly raw material freely available, were physically modified by atmospheric dielectric barrier discharge (DBD) plasma treatment of different dosages. The influence of the plasma treatment applied on the banana fibers was performed considering the mechanical properties, wettability, chemical composition and surface morphology. These properties were evaluated by tensile tests, static and dynamic contact angle, Fourier transform infrared spectroscopy, energy dispersive spectroscopy, X-ray diffractometry, conductivity and pH of aqueous extract, differential scanning calorimetry and scanning electron microscopy images. We compare untreated and treated fibers with three different DBD plasma dosages. The results of this study showed considerable modifications in banana fibers when these are submitted to plasma treatment.